2012
DOI: 10.1111/nph.12010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic variation creates potential for evolution of plant phenotypic plasticity

Abstract: SummaryHeritable variation in plant phenotypes, and thus potential for evolutionary change, can in principle not only be caused by variation in DNA sequence, but also by underlying epigenetic variation. However, the potential scope of such phenotypic effects and their evolutionary significance are largely unexplored.Here, we conducted a glasshouse experiment in which we tested the response of a large number of epigenetic recombinant inbred lines (epiRILs) of Arabidopsis thaliana -lines that are nearly isogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
273
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(284 citation statements)
references
References 77 publications
6
273
1
4
Order By: Relevance
“…While adaptation is accomplished by genetic changes through mutation, drift and selection are very slow for some introduced species, so epigenetic mechanisms can provide an alternative source of ecologically phenotypic diversity for rapid adjustment (Medrano, Herrera, & Bazaga, 2014). Epigenetic diversity can generate massive heritable variation of ecologically relevant plant traits such as root allocation, drought tolerance and nutrient plasticity (Zhang, Fischer, Colot, & Bossdorf, 2013), and it appears to increase the productivity and stability of plant populations in Arabidopsis thaliana under artificial conditions (Latzel et al., 2013). An increasing number of studies have also demonstrated the common existence and significant role of epigenetic variation in plant populations of herbs (Foust et al., 2016; Herrera, Medrano, & Bazaga, 2014; Medrano et al., 2014; Preite et al., 2015; Schulz, Eckstein, & Durka, 2014), shrubs (Avramidou, Ganopoulos, Doulis, Tsaftaris, & Aravanopoulos, 2015; Herrera & Bazaga, 2013, 2016), and trees (Guarino, Cicatelli, Brundu, Heinze, & Castiglione, 2015; Gugger, Fitz‐Gibbon, PellEgrini, & Sork, 2016; Lira‐Medeiros et al., 2010; Platt, Gugger, Pellegrini, & Sork, 2015; Sáez‐Laguna et al., 2014) under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While adaptation is accomplished by genetic changes through mutation, drift and selection are very slow for some introduced species, so epigenetic mechanisms can provide an alternative source of ecologically phenotypic diversity for rapid adjustment (Medrano, Herrera, & Bazaga, 2014). Epigenetic diversity can generate massive heritable variation of ecologically relevant plant traits such as root allocation, drought tolerance and nutrient plasticity (Zhang, Fischer, Colot, & Bossdorf, 2013), and it appears to increase the productivity and stability of plant populations in Arabidopsis thaliana under artificial conditions (Latzel et al., 2013). An increasing number of studies have also demonstrated the common existence and significant role of epigenetic variation in plant populations of herbs (Foust et al., 2016; Herrera, Medrano, & Bazaga, 2014; Medrano et al., 2014; Preite et al., 2015; Schulz, Eckstein, & Durka, 2014), shrubs (Avramidou, Ganopoulos, Doulis, Tsaftaris, & Aravanopoulos, 2015; Herrera & Bazaga, 2013, 2016), and trees (Guarino, Cicatelli, Brundu, Heinze, & Castiglione, 2015; Gugger, Fitz‐Gibbon, PellEgrini, & Sork, 2016; Lira‐Medeiros et al., 2010; Platt, Gugger, Pellegrini, & Sork, 2015; Sáez‐Laguna et al., 2014) under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of DNA methylation can affect ecologically important phenotypes and plasticity (Herrera & Bazaga, 2013; Nicotra et al., 2015; Zhang et al., 2013) and may play a significant role in adaptation to various habitat conditions (Foust et al., 2016; Richards et al., 2012; Schulz et al., 2014). For example, a naturally occurring epiallele named “NMR19‐4” has been discovered in Arabidopsis accessions , and its DNA methylation status is inheritable and independent of genetic variation (He et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2014); and (3) increasing evidence showing that epigenetic mechanisms are involved in phenotypic plasticity (Herrera and Bazaga 2013; Jablonka 2013; Zhang et al. 2013), which in turn plays a facilitating role in the colonization of fluctuating environments (Herrera et al. 2012; Lande 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms have been of interest in evolutionary biology (Richards et al, 2010;Zhang et al, 2013;Deans and Maggert, 2015), in the field of development (Beldade et al, 2011), and in such specialized fields as ecotoxicology (Vandegehuchte and Janssen, 2014). Historically, the research community has debated how to exactly define epigenetics (Deans and Maggert, 2015).…”
Section: Epigenetics-a Brief Overviewmentioning
confidence: 99%